What has Lapland to do with Tshwane? Ethics as the bridge between dogmatics and historical contexts - De Gruchy, John W. (HTS teologiese studies, 2015)
This article explores the question: what does it mean to do theology in South Africa today? It does so in three parts based on a narrative account of the author’s relationship with Johan Heyns from 1972–1990. In the first, the focus is on the reasons for and the significance of the transition of the Dogmatologiese Werkgemeenskap, in which Heyns played an influential role to the Theological Society of South Africa, of which the author was president from 1987–1992. In the second, the author examines the reason for this transition by comparing the role of Beyers Naudé with that of Heyns in doing theology, the one working outside the white enclave of the DRC, and the other from within. He then examines the criticism of Heyns’s theology which was expressed by J.J.F. Durand and which gave rise to the title of the article. In the final part of the article, the author reflects on the narrative in responding to the initial question on doing theology in context today. He highlights the importance of social location, of the willingness to transcend boundaries, and the need to regard the task of dogmatics and ethics as an integrated whole in responding prophetically to historical contexts.